Transitioning Escape Rooms to a Virtual Environment. (December 2021) - Kutzin, Jared M.; Sanders, Jenny E.; Strother, Christopher G.
Escape room: games have gained in popularity in both entertainment and education venues over the past several year. The global health pandemic put an abrupt end to in-person escape room programs due to the enclosed space in which they take place. In an attempt to continue to utilize the escape room concept we set about to create a virtual escape room: using commonly available software and assessed its usability and participant feelings about the experience. The results indicated that the participants thought the escape room was engaging (88%), that they had to work as a team (95%), and that they overall enjoyed the experience (85%). Virtual experiences cannot completely replace in-person experiences, but there are ways to introduce important teamwork and communication concepts to participants and make online meetings and conferences more engaging.